EVALUATION DE LA QUALITÉ INDUSTRIELLE DES ARGILES FIBREUSES DE BLED RMEL, BASSIN DU GHARB, MAROC - Bensalem, Hajar; Aadjour, Malika; El Hadi, Hassan; Saber, Najib; El Ouazzani, Ali.; Mouttaqi, Abdellah (European Scientific Journal, ESJ, 2014)
This work concerns the physico-chemical characterization and the industrial valuation of fibrous clays of the Eocene series of ‘Bled Rmel’, (Souk El Arbaa of Gharb area). Four specific samples were the object of analyses by X-rays, spectrometry, thermogravimetric analysis, and technological tests. The results confirm the relation between the composition of the clays and the quality of the final ceramic product. The chemical analysis made on four samples (BR1 to BR4) reveals their low content in Fe2O3 (lower than 3 %), a rate in alkaline reaching 3 % and a content in high silica (superior to 40 %). Al2O3 is lower than 4 % for samples BR1et BR2 while it is superior to 10 % for samples BR3 and BR4. The mineralogical analysis reveals very nearby mineralogical compositions. The thermogravimetric analysis underlines a bearable loss of weight, for four samples, due to the decomposition of the calcite and the dolomite. The technological tests on four samples (BR1 to BR4) indicate that products of clays sample BR1, BR2 and BR3 can be considered not refractory. In the other hand, the product of BR4 has very good quality and can be used for the manufacturing of ceramic products tiles, grounds and walls, pottery of service, etc.